The Role of School Field Introduction Program (PLP) in Developing Teaching Skills of Pre-Service Teachers at SD Negeri 231 Palembang - Liza Murniviyanti; Arizona Karno; Dodi Irawan; Nyi Ayu Anatasya; Dini Zaharani; Dwi Novi Fitrianingsih; Ria Aprianti; Sindi Sapitri; Reyhan Teska Anugrah (International Journal of Public Devotion, 2026)
The School Field Introduction Program (PLP) is an integral component in pre-service teacher education that aims to provide authentic experience in school environments. This study aims to analyze the role of the PLP program in developing the teaching skills of pre-service teachers at SD Negeri 231 Palembang, covering aspects of lesson planning, implementation, classroom management, use of instructional methods and media, and evaluation. The research employed a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. Research subjects consisted of PLP participants, cooperating teachers, and students. Results indicated that the PLP program plays a significant role in holistically improving students' pedagogical competencies. Participants demonstrated improvement in both technical and non-technical skills, such as confidence, communication ability, and adaptation to school environments. Challenges encountered included limited experience, class heterogeneity, and relatively short program duration. The PLP program is proven to be an effective vehicle for producing professional, competent pre-service teachers ready to face the dynamics of learning in elementary schools.Peran Program Pengenalan Lapangan Persekolahan (PLP) dalam Membentuk Keterampilan Mengajar Mahasiswa di SD Negeri 231 PalembangABSTRAKProgram Pengenalan Lapangan Persekolahan (PLP) merupakan komponen integral dalam pendidikan calon guru yang bertujuan memberikan pengalaman nyata di lingkungan sekolah. Penelitian ini bertujuan menganalisis peran program PLP dalam membentuk keterampilan mengajar mahasiswa di SD Negeri 231 Palembang, mencakup aspek perencanaan, pelaksanaan, pengelolaan kelas, penggunaan metode dan media pembelajaran, serta evaluasi. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi. Subjek penelitian terdiri dari mahasiswa peserta PLP, guru pamong, dan siswa. Hasil penelitian menunjukkan bahwa program PLP berperan signifikan dalam meningkatkan kompetensi pedagogik mahasiswa secara menyeluruh. Mahasiswa mengalami peningkatan keterampilan teknis maupun non-teknis, seperti kepercayaan diri, kemampuan komunikasi, dan adaptasi terhadap lingkungan sekolah. Kendala yang ditemui antara lain keterbatasan pengalaman, heterogenitas kelas, dan waktu pelaksanaan yang relatif singkat. Program PLP terbukti menjadi wahana efektif dalam mencetak calon guru yang profesional, kompeten, dan siap menghadapi dinamika pembelajaran di sekolah dasar.Kata Kunci :PLP; keterampilan mengajar; mahasiswa calon guru; sekolah dasar; kompetensi pedagogik